Tip Lesion Most Frequent FSGS Variant Related to COVID-19 Vaccine: Two Case Reports and Literature Review - Emmy Marjorie Carvalho de Araújo; Marcos Adriano Garcia Campos; Andressa Monteiro Sodré; Maria Izabel de Holanda; Rodrigo Hagemann; Antonio Augusto Lima Teixeira Júnior; Natalino Salgado Filho; Precil Diego Miranda de Menezes Neves; Gyl Eanes Barros Silva (Vaccines, 2024)
Large-scale COVID-19 vaccination has been one of the most effective strategies to control the spread of the SARS-CoV-2 virus. However, several cases of glomerular injury related to the COVID-19 vaccine have been described in the literature. We report two cases of a tip lesion variant of focal segmental glomerulosclerosis (FSGS), which presented with significant proteinuria and improved after immunosuppression. In our literature review, the tip lesion variant of FSGS is currently the most frequent variant associated with vaccination against COVID-19. Prognosis is favorable and without significant alterations in the tubulointerstitial or vascular compartments. Adverse effects of vaccines need to be recognized early and will help us to understand the immune and pathological mechanisms of kidney damage.